Pengaruh Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan Pada Perusahaan Sektor Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Natalia, Novia; Silaban, Adanan; Sihombing, Halomoan S. (CV. ITTC INDONESIA, 2024)
This study aims to examine the influence of company size and asset structure on capital structure in food and beverage This research is a quantitative research with the type of data source being secondary data obtained from the company's financial statements and annual reports. The analysis method used is multiple linear regression using SPSS version 26 software. Data testing was carried out using descriptive statistical analysis, classical assumption test, simple linear regression analysis test, determination coefficient and t-test. The independent variable used in this study is Corporate Social Responsibility (CSR) while the dependent variable is financial performance proxied by Return On Asset (ROA). The results of the study show that Corporate Social Responsibility (CSR) has a positive and significant effect on financial performance. In addition, based on the determination coefficient (R2) test, Corporate Social Responsibility (CSR) was able to explain its influence on financial performance by 12.2% of the dependent variables. Based on the results of the study, it was concluded that financial performance measured using the return on asset ratio had a positive and significant effect on Corporate Social Responsibility (CSR). Suggestions that can be given for future research are to add variables that are not included in this study that are considered to affect Corporate Social Responsibility (CSR) and increase the research period to get accurate results.